Can underwater endoscopic mucosal resection be an alternative to conventional endoscopic mucosal resection for superficial non‐ampullary duodenal epithelial tumors? - Hidenori Tanaka; Yuji Urabe; Hiroki Takemoto; Kazuki Ishibashi; Hirona Konishi; Yuka Matsubara; Yudai Takehara; Shin Morimoto; Fumiaki Tanino; Noriko Yamamoto; Hajime Teshima; Junichi Mizuno; et al. (DEN Open, 2024)
Abstract Objectives Underwater endoscopic mucosal resection (UEMR) is a simpler procedure for superficial non‐ampullary duodenal epithelial tumors (SNADET) than conventional endoscopic mucosal resection (cEMR). This study aimed to evaluate whether cEMR can be substituted by UEMR for SNADET in terms of effectiveness, safety, and learning curve. Methods A total of 157 consecutive patients with 203 SNADETs ≤20 mm in diameter, including 107 lesions resected by cEMR and 96 lesions resected by UEMR, between January 2019 and May 2023, were retrospectively recruited. The treatment outcomes were compared between the cEMR and UEMR groups. The risk factors for incomplete resection by UEMR were analyzed using univariate and multivariate analyses. Lesions in the UEMR group were divided chronologically into five periods; thereafter, the en bloc resection rate and procedure time were compared. Results No significant differences existed between the cEMR and UEMR groups in the mean procedure time (3.9 min vs. 3.6 min, p = 0.1380) or en bloc resection rate (91% vs. 94%, p = 0.4138). No perforation was observed in either group. Tumor size was an independent risk factor for incomplete resection using UEMR (p < 0.01). The history of biopsy was not associated with incomplete resection using UEMR. The en bloc resection rate of UEMR was 100% (20/20) in the first period and ranged from 90% to 100% over all periods. Conclusion UEMR is safe and effective for SNADET ≤20 mm, regardless of a history of biopsy, and is easy to learn. Thus, UEMR can serve as an alternative to cEMR.